Collaborative Governance in Empowering MSMEs to Advance in Class in Pacitan - Muhammad Eko Atmojo; Awang Darumurti; Nita Ariba Hanif (Universitas Muhammadiyah Tangerang, 2023)
The purpose of this study is to find out how big the role of the government and the government's response to realizing policies that favor MSME actors. This study uses the Qualitative Data Analysis Software (QDAS) method with the help of Nvivo12 Plus tools. The data source for this research comes from primary data and secondary data taken through interviews, observation, and documentation techniques. This research data processing uses a Crosstab Query to help visualize data and analyze Twitter data. Data analysis in this study uses the interactive model technique which begins with data coding as the reduction stage, data visualization, and drawing conclusions as the final findings. The results of the study can be concluded that the Pacitan Regency Government provides assistance to MSMEs through collaboration with various stakeholders. Where this collaboration begins with the identification of problems that hinder the development of MSMEs in Pacitan Regency. Where the collaboration that exists with the private sector, BUMN and other stakeholders is still focused on marketing issues, but for other problems, it has not been widely collaborated and managed between partners and the Pacitan Regency Government.Â Tujuan penelitian ini adalah untuk mengetahui seberapa besar peran pemerintah dan respon pemerintah dalam mewujudkan kebijakan yang berpihak pada pelaku UMKM. Â Penelitian ini menggunakan metode Qualitative Data Analysis Software (QDAS) dengan bantuan alat Nvivo12 Plus. Sumber data penelitian ini berasal dari data primer dan data sekunder yang diambil melalui teknik wawancara, observasi, dan dokumentasi. Pemrosesan data penelitian ini menggunakan Crosstab Query untuk membantu memvisualisasikan data dan menganalisis data Twitter. Analisis data dalam penelitian ini menggunakan teknik model interaktif yang diawali dengan pengkodean data sebagai tahap reduksi, visualisasi data, dan penarikan kesimpulan sebagai temuan akhir. Hasil penelitian dapat disimpulkan bahwa Pemerintah Kabupaten Pacitan memberikan pendampingan kepada UMKM melalui kolaborasi dengan berbagai pemangku kepentingan. Dimana kerjasama ini diawali dengan identifikasi permasalahan yang menghambat perkembangan UMKM di Kabupaten Pacitan. Dimana kerjasama yang terjalin dengan swasta, BUMN dan stakeholder lainnya masih terfokus pada isu pemasaran, namun untuk permasalahan lainnya belum banyak kerjasama dan dikelola antara mitra dengan Pemerintah Kabupaten Pacitan.Â